A behavioral analysis of habituation and sensitization of shortening in the semi-intact leech - Boulis, NM (J Neurosci, 1988)
We have previously demonstrated that the shortening reflex of the leech Hirudo medicinalis displays habituation, dishabituation, and sensitization. In this paper we demonstrate that the shortening reflex of the semi-intact animal also displays these phenomena. In the first experiment we found that the magnitude of the touch-elicited shortening reflex decreased as a result of repeated stimulations of the skin every 2 min. The second experiment examined the change in this reflex as a function of the interstimulus interval (ISI). The reflex failed to decrease when the ISI was 10 sec, but decreased significantly when the ISI was either 45 or 360 sec. Finally, in a third experiment we found that the presentation of noxious stimuli prior to habituation training prevented habituation. Thus, as we have observed previously in the intact animal, the semi-intact animal displays habituation, dishabituation, and sensitization.